Factor Affecting Purchase Intention of Health Supplement in Malaysia - Tan, Ying Ling; Wong, Chee Hoo; Ng, Alex, Hou Hong; Lim, Kim Yew (INTI International University, 2019)
This research was initiated to bridge the gap by determining the factors that influence the purchase intention health supplement in Malaysia and thus provide insights about the marketing plan to the marketers in the health supplement industry to improve their competitiveness. Questionnaires were distributed to 386 individual by convenience sampling in Malaysia via social media such as Facebook and Whatsapp. Besides, correlation study and multiple regression were applied as the research method. Among five independent variables, only informational influence showed the insignificant result on purchase intention of health supplement in Malaysia, while perceived price showed negative relationship on purchase intention of health supplement in Malaysia.